Maternal Factors Associated with Nutritional Status Of 1-5 Years Children Residing in Field Practice Area of Rural Health Training Centre Naila, Jaipur (Rajasthan) India - Lokesh Sonkaria; Afifa Zafer; Kusum Lata Gaur; Ravindra Kumar Manohar (Medsci Publications, 2014)
Background: Good nutrition benefits families, their communities and the world as a whole. Maternal factors are important in maintaining the nutrition of 1-5 year children. Objective: To ascertain the association of maternal factors with nutrition of 1-5 year children. Materials and Methods: A community based cross sectional descriptive type of observational study was carried out in the field practice area of RHTC Naila in Jaipur district of Rajasthan. 30 Cluster sampling technique was used to cover whole field practice area of RHTC. 330 children 1-5 years were selected from clusters were. These children were examined and their mothers were interviewed. Information about nutritional status of children with relevant socio‑demographic data were also collected. To find out associating factors chi-square tests of significance were used. Results: Out of total 330 children 43 i.e. 13.03% were under-nourished. Undernourished children were more in children of 26-30 years age group mothers than extremes of reproductive ages (P<0.001). Likewise undernourishment was found more in children of illiterate mothers (<0.05) and children of mothers having less birth spacing (P<0.05). Maternal BMI, maternal occupation, maternal age at marriage, maternal age at consummation, maternal age at 1st child birth and maternal anemia were not found to be associated with nutritional status of children. Conclusion: Nutrition status of children was associated with maternal age, maternal education and spacing between children whereas it was not associated with maternal BMI, maternal occupation, maternal age at marriage, maternal age at consummation, maternal age at 1st child birth and maternal anemia.